2009
DOI: 10.1038/nature07822
|View full text |Cite
|
Sign up to set email alerts
|

Toxin B is essential for virulence of Clostridium difficile

Abstract: Clostridium difficile is the leading cause of infectious diarrhea in hospitals worldwide, because of its virulence, spore-forming ability and persistence1,2. C. difficile-associated diseases (CDAD) are induced by antibiotic treatment or disruption of the normal gastrointestinal flora3,4. Recently, morbidity and mortality resulting from CDAD have increased significantly due to changes in the virulence of the causative strains and antibiotic usage patterns1,2,5,6. Since 2002, epidemic toxinotype III NAP1/027 str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
552
3
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 666 publications
(575 citation statements)
references
References 37 publications
17
552
3
3
Order By: Relevance
“…2a,b). We reasoned that this may occur due to increased expression of toxin A by the A + B -mutant; a phenomenon which has been reported previously 4 . Indeed, qRT-PCR analysis confirmed that expression of toxin A was an average of 3.3-fold greater in the A + B -mutant than the A + B + parental strain (data not shown).…”
mentioning
confidence: 92%
“…2a,b). We reasoned that this may occur due to increased expression of toxin A by the A + B -mutant; a phenomenon which has been reported previously 4 . Indeed, qRT-PCR analysis confirmed that expression of toxin A was an average of 3.3-fold greater in the A + B -mutant than the A + B + parental strain (data not shown).…”
mentioning
confidence: 92%
“…2 Although toxin B is the determinant of pathogenicity, 16 testing for both toxins can potentially add sensitivity to an assay, because of the differential lability of toxins in feces. 43 Most of the EIA assays were compared with CCCN during initial evaluations, which made the test appear to have adequate sensitivity for routine laboratory use.…”
Section: Eia Methodsmentioning
confidence: 99%
“…The toxins are regulated by two additional genes, tcdC and tcdR; a holinlike protein is also encoded by tcdE. 15 According to an elegant series of experiments by Lyras et al, 16 toxin B is the most critical determinant of pathogenicity for human infections. Although this has been recently challenged by Kuehne et al, 17 studies by Leav and colleagues 18 support the critical role of toxin B in infection, noting that patients with low levels of antibody specific for toxin B, but not for toxin A, are more likely to have recurrent disease.…”
Section: Organism Descriptionmentioning
confidence: 99%
“…La seconde étape repose sur la production par les souches toxinogènes de C. difficile des toxines A (ou TcdA) et B (ou TcdB) qui sont dotées à la fois de propriétés entérotoxiques et cytotoxiques et qui agissent en synergie. Des données récentes, utilisant des mutants de toxines, suggèrent que seule TcdB serait un facteur de virulence essentiel [2]. TcdB et TcdA sont des glucosyltransférases qui catalysent la monoglucosylation de la thréonine en 35/37 des petites GTPases Rho, Rac et Cdc42 des cellules cibles [3].…”
unclassified